Oath in Legal Tradition as a Reflection of Value System of Russian Peasantry (Mid-19th to Early 20th Century) - T. V. Bauer (Научный диалог, 2024)
This article examines oaths functioning within customary law during the post-reform period, reflecting the system of basic values of the peasant society. The relevance of the study is justified by the urgent task of preserving ethnocultural identity, as well as the practical needs of the modern legal system, demonstrating a disconnect from the value orientations of traditional culture. The sphere and peculiarities of oath application in customary legal tradition are identified, and the main elements of the ritual are described. The verbal component of oaths is identified and characterized. The attitudes of peasants towards oaths are explored, and beliefs about the consequences of false oaths are analyzed. The system of values relevant to peasant society is reconstructed, highlighting justice, life (including a “righteous” life after death), health, reputation, honor, prosperity, various social ties including familial connections uniting ancestors and descendants as well as intra-community bonds, and spiritual values such as the connection with God, the rupture of which was perceived as spiritual death. It is concluded that despite the declining popularity of informal oaths, they remain relevant in the post-reform period as a means of conflict neutralization and an effective mechanism for uncovering truth, precisely because they appeal to significant categories and values for ethnocultural consciousness.